Preschool Prosocial Behavior in Countries of The Andean Community - Cruz-Montero, Juana (2021)
Scientific interest lies in studying the prosocial characteristics of the child population of the Andean Community (Latin America), as it is a humanistic requirement in currently convulsed societies. In this sense, the research compares the prosocial behavior of 579 infants from Peru, Ecuador and Bolivia. We use rubrics and observation cards. Formal educational institutions host more prosocial children, with boys being better. Individuals from Bolivian and Ecuadorian schools have better prosocial behavior. In terms of management, private institutions in Peru develop a higher level of this behavior. In the Peruvian infants indecipherable empathy was detected, a certain percentage of Bolivians presented a low level of socialization; another percentage of Ecuadorians presented indecipherable cooperation behaviors.